Butoh : cradling empty space - Vangeline (New York Butoh Institute, 2020)
Butoh, a performance art form that grew out of the Japanese avant-garde scene of the 1950s, has traveled from east to west over the last 60 years, growing in popularity as it evolves. With origins in modern dance, French mime, and the surrealist movement, this fascinating postmodern dance genre is often thought of as mysterious and is frequently misunderstood. Through twenty years of research, interviews with some of the world's top practitioners, historical documents, and rare photographs, Vangeline shines a light on this "dance of darkness." New revelations include the under-represented role of women in the development of the form, the connection between butoh and neuroscience, and the cross-cultural perspective of international influences on the evolution of the dance. Butoh: Cradling Empty Space will appeal to dance students, teachers, performance art scholars, movers, and anyone interested in choreography, theater, and Japanese history, culture and art.